Covalent immobilization of laccase in green coconut fiber and use in clarification of apple juice - Souza Bezerra, Thais Milena de [UNESP]; Bassan, Juliana Cristina [UNESP]; Oliveira Santos, Victor Tabosa de; Ferraz, Andre; Monti, Rubens [UNESP] (Elsevier B.V., 2015)
Waste materials from agroindustry constituted from lignocellulose have been used in the immobilization process of technological interest enzymes to reduce costs, increasing the value of such products. In the present study, green coconut husk was used to obtain fibers (CF) that were treated through thermal decompression in combination with either acid or alkaline medium. A solid support for enzyme immobilization was prepared using the pretreated CF activated with glyoxyl or glutaraldehyde and was used to immobilize the laccase enzyme (EC 1.10.3.2) produced by Trametes versicolor. Immobilized enzyme retained up to 59 +/- 1% of the initial activity and showed maximum immobilization profile of 98 +/- 1%. The thermal stability was higher when laccase was immobilized on alkaline pretreated support with increments of 6.8-fold (laccase-glutaraldehyde-FC) up to 16.5-fold (laccase-glyoxyl-FC) of the soluble enzyme. The laccase-glutaraldehyde-CF achieved excellent results in the clarification of apple juice, reducing 61 +/- 1% of the original juice color and 29 +/- 1% of its turbidity, retaining up to 100% of the initial activity after a 10-times reuse assay. This study is pioneer in the utilization of low-cost support for laccase immobilization with application in the juice fruits clarification. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Laccase; Trametes versicolor; Coconut fiber; Enzyme immobilization; Apple juice